2001
DOI: 10.2337/diacare.24.9.1528
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Incidence of Type 2 Diabetes in Older Iowa Women

Abstract: OBJECTIVE -To examine the associations between reported intakes of dietary fat and incident type 2 diabetes.RESEARCH DESIGN AND METHODS -We studied the relation between dietary fatty acids and diabetes in a prospective cohort study of 35,988 older women who initially did not have diabetes. Diet was assessed with a food frequency questionnaire at baseline, and 1,890 incident cases of diabetes occurred during 11 years of follow-up. RESULTS -After adjusting for age, smoking, alcohol consumption, BMI, waist-to-hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
267
12
16

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(319 citation statements)
references
References 50 publications
24
267
12
16
Order By: Relevance
“…Fiber specifically derived from vegetables or fruit has, however, not been associated with diabetes risk (Colditz et al, 1992;Montonen et al, 2003). Margarine and oil intake was associated with a reduced diabetes risk in our study, which is in line with the results of previous epidemiological studies that have found an association between the intake of vegetable fat and decreased diabetes risk (Colditz et al, 1992;Vessby et al, 1994;Meyer et al, 2001;Salmeron et al, 2001). The type of dietary fat may play a role in diabetes development by modifying the fatty acid composition of the phospholipid cell membrane, which may affect insulin receptor properties and glucose transportation (Storlien et al, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Fiber specifically derived from vegetables or fruit has, however, not been associated with diabetes risk (Colditz et al, 1992;Montonen et al, 2003). Margarine and oil intake was associated with a reduced diabetes risk in our study, which is in line with the results of previous epidemiological studies that have found an association between the intake of vegetable fat and decreased diabetes risk (Colditz et al, 1992;Vessby et al, 1994;Meyer et al, 2001;Salmeron et al, 2001). The type of dietary fat may play a role in diabetes development by modifying the fatty acid composition of the phospholipid cell membrane, which may affect insulin receptor properties and glucose transportation (Storlien et al, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that as the intake of industrially produced trans fatty acids in the USA is on average 3% energy, a reduction in trans fatty acid intake of 2% energy could reduce the incidence of type-II diabetes by 40% if the fats containing the trans fatty acids were consumed in their original unhydrogenated form. It was not possible, however, to find such an association in either the Iowa Women Study (Meyer et al 2001) or the Health Professional's Study (Wahle and James 1993). Studies carried out at National Institute of Nutrition (NIN), Hyderbad, India to evaluate the effects of TFA from vanaspati in rats showed that both saturated fatty acids (SFA) (5 g/100 g,10% energy) and TFA (3% energy) increased insulin resistance (decreased insulin sensitivity).…”
Section: Health Risks Of Trans Fatty Acidsmentioning
confidence: 99%
“…Physical activity was categorized as: none; low; moderate; or high. Cigarette smoking status was defined as: never smoked; ex-smoker; smoker (,10 cigarettes/d); smoker (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (19) . Alcohol consumption was classified according to National Health and Medical Research Council classifications as: non-drinker; low-risk drinker (#14 drinks/week); risky drinker (15-28 drinks/ week); or high-risk drinker (.28 drinks/week) (20) .…”
Section: Other Measurementsmentioning
confidence: 99%